The Development Teacher Role and Counseling at Madrasah Ibtidaiyyah - Elihami Elihami; Mohd. Melbourne (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
The purpose of this study is to investigate a new approach to develop teachers’ soft skills and provide counseling guidance for students at Madrasah Ibtidaiyah Darud Da'wah wal Irsyad (MI DDI). The research employed a qualitative case study using a bibliographic design with systematic and explicit mapping methods. Data was collected through semi-structured interviews to examine the learning method. The findings show that the innovation role of an Islamic religious education teacher includes counseling activities for students. The collaborative implementation in terms of role between the religious teacher and counselor roles is essential for the successful development of this approach. This research contributes to the development of a new learning method for soft skills and counseling guidance for elementary school students. It demonstrates an effective and efficient strategy to teach and improve teachers’ soft skills by integrating soft skill training into courses focused on hard skills.